1997
DOI: 10.1001/archsurg.1997.01430360083015
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Vitamin E Supplementation Inhibits the Cytokine Response to Endotoxin

Abstract: Our data demonstrate that a short-term, high-dose enteral supplementation of vitamin E can modulate the monocyte and macrophage response to endotoxin. These data, along with other animal studies showing a protective effect of vitamin E treatment in sepsis and ischemia-reperfusion injury, suggest a potential role for vitamin E supplementation in patients at risk of the systemic inflammatory response syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Conversion of the 18-carbon n-6 fatty acid arachidonic acid into PGE 2 is facilitated by transcription of cyclooxygenase-2 (COX-2) on signaling mechanisms through proinflammatory cytokines such as TNF-α or IL-1β (Rivest, 2010;Kalinski, 2012). In a study using LPS-stimulated rats, 100 mg of Vit E supplementation depressed TNF-α production in peritoneal macrophages and the degree of TNF-α suppression was correlated to serum Vit E levels (Bulger et al, 1997). A mouse study also demonstrated that 500 mg Vit E supplementation reduced age-related ex vivo production of PGE 2 in a spleen homogenate (Meydani et al, 1986;Wu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of the 18-carbon n-6 fatty acid arachidonic acid into PGE 2 is facilitated by transcription of cyclooxygenase-2 (COX-2) on signaling mechanisms through proinflammatory cytokines such as TNF-α or IL-1β (Rivest, 2010;Kalinski, 2012). In a study using LPS-stimulated rats, 100 mg of Vit E supplementation depressed TNF-α production in peritoneal macrophages and the degree of TNF-α suppression was correlated to serum Vit E levels (Bulger et al, 1997). A mouse study also demonstrated that 500 mg Vit E supplementation reduced age-related ex vivo production of PGE 2 in a spleen homogenate (Meydani et al, 1986;Wu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, extensive in vitro data support the relationship between oxidative stress and the induction of genes integral to the systemic inflammatory response, including TNF-␣, IL-1, IL-8, and ICAM-1, putatively mediated through activation of the nuclear transcription factor NF-B. 2,31,32 Several in vivo studies document a clear benefit to antioxidant supplementation in animal models of endotoxemia, ARDS, and reperfusion injury 4,5,[33][34][35][36][37] and have confirmed that there is a relationship between oxidative stress and NF-B activation in vivo. 4 The importance of oxidative stress in the early phases of critical illness is underscored by the relative antioxidant depletion reported in many observational studies of this population.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo this vitamin is able to modify monocyte cytokine production [12,13] . The randomized controlled trial SPACE suggested a potential benefi t of vitamin E on the incidence of cardiovascular events in hemodialysis patients [14] .…”
Section: Introductionmentioning
confidence: 99%